The role of idioms in reducing depression in university students: a study on group cognitive behavioral therapy - Chenchen Lin; Mingyu Hu; Jingren Xu; Ruilu Yang; Haoran Yu; Hua Yang; Ning Zhang (BMC Psychology)
Abstract Purpose To evaluate the effectiveness of Culturally Adapted Cognitive-Behavioral Therapy (CA-CBT) compared to standard CBT in alleviating depression in college students. Methods A randomized trial was conducted on college students with mild to moderate depression. The CA-CBT group (21 students) received a group CA-CBT intervention incorporating idioms, while the standard CBT group (20 students) received a standard group-based CBT intervention. Both group interventions were conducted once a week, with each session lasting one and a half hours, for a total duration of eight weeks. Eighteen students from the standard CBT group and 12 from the CA-CBT group completed the trial. Depressive symptoms, cognitive distortions, emotional regulation, and CBT understanding were assessed at baseline, week five, post-treatment, and three months after post-treatment using validated scales. Data were analyzed using repeated measures ANOVA, t-tests, and chi-square tests via SPSS 26.0. Results The repeated measures ANOVA results for the pre-treatment and post-treatment showed a significant interaction effect of time and intervention and a significant main effect of time for the sleep disturbance factor of the Hamilton Depression Rating Scale. However, only the main effect of time was significant for all other variables. T-tests indicated that the CA-CBT group had significantly lower Hamilton scores at follow-up compared to the standard CBT group. Meanwhile, the standard CBT group had significantly better CBT understanding post-treatment. Except for the above two items, no other significant difference were found by T-test. Conclusions Compared with standard CBT, the CA-CBT group that incorporates idioms is beneficial for college students with depressive symptoms to continue to achieve relief for a certain period of time after the end of treatment. Specifically, this relief may be reflected in the improvement of sleep problems. However, CA-CBT did not better improve participants’ emotion regulation, understanding of cognitive behavioral therapy, or reduction of cognitive distortions.At the same time, the CA-CBT group did not perform better than the standard CBT group in terms of dropout rate, treatment satisfaction, recommendation, and re-use rate. Trial registration The trial was registered on the Chinese Clinical Trial Registry (No. ChiCTR2300074752|| http://www.chictr.org.cn/ ) on August 15, 2023.